FORMULATION AND DEVELOPMENT OF RUTIN PHYTOSOMAL COMPLEX FOR DIABETES (International Journal of Food and Nutritional Sciences, 2022)
Medicinal plants have been a major source of cure of human diseases since time immemorial. The demand for the plant derived drugs seems to increase in developing countries due to their medicinal value and economic procurement. Plants have been used in a wide variety of dosage form as diabetes is chronic and non-curable disease, regular treatment is needed. Till now, no work has been carried out on preparation of rutin - phytosome (rutin- Phytosomal complex) for the treatment of diabetes. So, the present work aimed to formulation and development of rutin-phytosome (rutin-phospholipid complex) for diabetes and to compare in vitro and in vivo activity of rutin and rutin -phytosome (rutin - phospholipid complex).